Pengaruh Pemberian Pupuk Organik Urin Kelinci Terhadap Pertumbuhan Tanaman Kangkung Darat (Ipomoea Reptans): The Effect of Rabbit Urine Organic Fertilizer on The Growth of Land Kale Plants (Ipomoea Reptans) - Via Rahmatul Ummah; David Septian Sumanto Marpaung (Politeknik Pertanian Bogor, 2022)
The use of organic fertilizer is one solution to solve the problem of lack of nutrients in the soil, taking into account the sustainability aspect. Rabbit droppings are obtained from rabbit breeders at P4S Agro Cendekia Bangunrejo. The study was conducted in July 2021 at P4S Agro Cendekia Bangunrejo. Liquid organic fertilizer is made by two different methods namely Y1 (a mixture of 10 liters of rabbit urine, 150 grams of brown sugar and 0.2 liters of EM3) with a fermentation time of 7 days and a pH of 7.5 and Y2 (a mixture of 10 liters of rabbit urine, 150 grams of brown sugar, 0.2 liters of EM3 and bamboo root) with a fermentation time of 6 days and a pH of 7.3. There are three treatments, namely P1 as an experimental control (without the provision of liquid organic fertilizer), P2 is given liquid organic fertilizer Y1, P3 is given liquid organic fertilizer Y2. Each treatment was randomly taken as many as 5 samples to be used as the object of the study. The parameters of the growth of kale plants analyzed after 10 hst (days after planting) are plant height, number of leaves, length of roots and number of roots. From the research data obtained, the highest average plant height is in the P2 treatment with a value of 8.12 cm. The average number of leaves is the largest in the P2 treatment as many as 5 stems. The average length of the highest root is in P3 at 8.46 cm. The average number of roots obtained in the P2 treatment is 29 branches. Liquid organic fertilizer of rabbit urine affects the growth of kale plants. Keywords: Growth, growth of rabbit urine, rabbit urine